Investigations into Ti–(Nb, Ta)–Fe alloys for biomedical applications. (1st March 2016) - Biesiekierski, Arne; Lin, Jixing; Li, Yuncang; Ping, Dehai; Yamabe-Mitarai, Yoko; Wen, Cuie
Graphical abstract: Abstract: In this study, a Ti–(Ta, Nb)–Fe system was investigated with aims toward the development of high strength, biocompatible titanium alloy suitable for the development of porous orthopedic biomaterials with minimal processing. Notable findings include yield strengths of 740, 1250 and 1360 MPa for the Ti–12Nb–5Fe, Ti–7Ta–5Fe and Ti–10Ta–4Fe alloys, respectively, with elastic moduli comparable to existing Ti-alloys, yielding admissible strains of 0.9 ± 0.3, 1.2 ± 0.2 and 1.13 ± 0.02% for the Ti–12Nb–5Fe, Ti–7Ta–5Fe and Ti–10Ta–4Fe alloys, respectively; more than twice that of human bone. Observed microstructure varied significantly depending on alloy; near pure β -phase was seen in Ti–12Nb–5Fe, β with some ω precipitation in Ti–10Ta–4Fe, and a duplex α + β structure was observed throughout the Ti–7Ta–5Fe. In addition to suitable mechanical parameters, all investigated alloys exhibited promising corrosion potentials on the order of −0.24 V SCE, equalling that seen for a C.P.-Ti control at −0.25 V SCE, and substantially more noble than that seen for Ti–6Al–4V. Electrochemical corrosion rates of 0.5–3 μ m/year were likewise seen to agree well with that measured for C.P.-Ti. Further, no statistically significant difference could be seen between any of the alloys relative to a C.P.-Ti control regards to cell proliferation, as investigated via MTS assay and confocal microscopy. As such, the combination of high admissible strain and low corrosion indicate all investigated alloys show significant promise as potential porous biomaterials while in the as-cast state, with the Ti–10Ta–4Fe alloy identified as the most promising composition investigated. Statement of Significance: The findings of this paper are of significance to the field of metallic biomaterials as they detail the development of alloys of satisfactory biocompatibility and electrochemical behaviour, that furthermore display exceptional mechanical properties. Notably, both extremely high compressive yield strengths and admissible strains, up to 1.36 GPa and 1.2% respectively, are reported, exceeding or rivalling that seen in traditional alloys such as Ti–6Al–4V, which typically displays compressive yield strengths and admissible strains on the order of 895 MPa and 0.81% respectively, as well as modern alloys such as Gum Metal or TNZT. That this is achieved in the absence of thermomechanical processing represents a significant and novel outcome of substantial benefit for application as a porous biomaterial.